Pengaruh Beban Pajak Tangguhan, Kepemilikan Manajerial Dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Polin Perubahan Telaumbanua; Nani Mulyani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to examine the effect of deferred tax expense, managerial ownership, and firm size on firm value. In this research, the independent variables used are deferred tax expense, managerial ownership, and firm size, while the dependent variable is firm value. The study was conducted using a sample of Property and Real Estate companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. The type of data used in this research is secondary data in the form of audited financial statements published by the Indonesia Stock Exchange (IDX) from 2020 to 2024. The sample was selected using a purposive sampling method, resulting in 10 companies observed over 5 years, producing a total of 50 firm-year observations. Data processing was conducted using Microsoft Office Excel and EViews 12 statistical software by performing descriptive statistical analysis, model feasibility tests, classical assumption tests, coefficient of determination tests, panel data regression analysis, F-test, and t-test. The results of the F-test indicate that deferred tax expense, managerial ownership, and firm size simultaneously affect firm value. Furthermore, the t-test results show that deferred tax expense, managerial ownership, and firm size each have a significant effect on firm value